We can write 25+(-4)+(-6) as-

** 25 - 4 - 6**

**= 21 - 6**

**= 15 **

**Thus, 25+(-4)+(-6) equals to 15**

We can write 25+(-4)+(-6) as-

** 25 - 4 - 6**

**= 21 - 6**

**= 15 **

**Thus, 25+(-4)+(-6) equals to 15**

25+(-4)+(-6) equal 15

x + (-y) is the same as saying x - y

25 + (-4) is the same as saying 25-4

25-4=21

21 + (-6) is the same as saying 21-6

21-6=15.

Yes, 15 is the answer that you are looking for :)

According to Cortana, yes.

25+(-4)+(-6) equal 15

x + (-y) is the same as saying x - y

25 + (-4) is the same as saying 25-4

25-4=21

21 + (-6) is the same as saying 21-6

21-6=15.

Yes, 15 is the answer that you are looking for :)

Leslie Colpa

köpa kreatin

Monroe-born Vencel Reichelt is interested in new kung fu, renting movies. Also, he loves going out with his solid friends.

new gets perfect

Monroe-born Vencel Reichelt is interested in new kung fu, renting movies. Also, he loves going out with his solid friends.

new gets perfect